Kajian Dalam Pengawasan Sistem Parkir Elektronik di Kota Bandung - Yogi Gumilar Saeful Akbar (Publikasi Indonesia, 2022)
Decentralization has granted local governments the right to control fund from original local government revenue (Pendapatan Asli Daerah - PAD). A significant source of local revenue in Bandung comes from parking fees. Since 2017, the Municipal Government of Bandung has innovated parking retribution management by implementing an electronic parking machine system for several parking locations located along the side of the road. However, a problem arises when the parking machine in Bandung does not substantially enhance parking management. This study aims to examine the supervision undertaken by the Bandung city government for the implementation of electronic parking machines. This study was conducted on the implementation of an electronic parking system using supervisory theory. Several hindrance factors and problems were identified due to the state of the city government's supervision of electronic parking machines. Inadequate supervision and poor reporting by field officers lead to illegal levies and damage to electronic parking machines. It was determined that improving coordination between the Department of Transportation and other relevant agencies, such as the Bandung City Revenue Service and the Civil Service Police Unit, would improve the supervision quality. Developing specific rules and regulations to regulate electronic parking machines is necessary.